The Influence of Income and Total Cash Flow to Stock Price - Sherlita, Erly; Annur, Firman (CENTRAL ASIA AND THE CAUCASUS, 2022)
The study aims to determine the influence of accounting profit and total cash flow to stock price on miscellaneous industry company listed on the Indonesia Stock Exchange period 2016-2018. Seen from the factors tested in the study are the relationship between accounting profit and total cash flow in affecting stock price. The research uses non probability sampling technique, which is purposive sampling to get 22 samples from 51 on miscellaneous industry. While the method of analysis used were thr estimation model, classical assumption, regression analysis of panel data, and hypothesis test using t-statistic hypothesis test to test partial regression coefficient and F-statistic to test the simultaneous regression coefficient with 5% significance level. The results of this research partially showed that accounting profit significantly affect on stock price, while the total cash flow does not significantly affect on stock price. Simultaneously accounting profit and cash flow significantly affect on stock price.